2019
DOI: 10.1117/3.2510243
|View full text |Cite
|
Sign up to set email alerts
|

Field Guide to Solid State Physics

Abstract: Primitive Cell A substance is considered to be in a crystalline state (known as a crystal) if its constituent atoms are arranged in a regular and repetitive pattern. Crystals can be described by an object that, when repeated, generates the entire crystal. Such an object can be considered as a "building block" called a unit cell. The unit cell is spanned by three independent vectors a 1 , a 2 , and a 3 , which may or may not lie along the Cartesian coordinate axes. It contains only one lattice point, and its vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2(a), it is observed that the waveguide mode is symmetric, so the absorbed power and consequently the generated carriers as a function of space are symmetric. Diffusion is a mechanism that contributes to the flow of the current when there is a gradient of carrier concentration [53]. Considering the symmetric distribution of the generated carriers and the symmetric doping profile across the photodetector cross-section (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…2(a), it is observed that the waveguide mode is symmetric, so the absorbed power and consequently the generated carriers as a function of space are symmetric. Diffusion is a mechanism that contributes to the flow of the current when there is a gradient of carrier concentration [53]. Considering the symmetric distribution of the generated carriers and the symmetric doping profile across the photodetector cross-section (see Fig.…”
Section: Methodsmentioning
confidence: 99%